Gemas Si Botak (Gerakan Bersama Imunisasi Booster pada Anak) dalam Meningkatkan Cakupan Imunisasi Booster 18 Bulan - Brivian Florentis Yustanta; Sekar Melati Aisyah Putri (STIKES dan AKZI Karya Husada Kediri, 2022)
In 2021, around 1.7 million Indonesian children do not have complete routine immunization status. Complete basic immunization coverage in Dukuh Dimoro Village, Mojoagung Sub-district, Jombang Regency has only reached 58.4% of the target of 79.1%. The aim of this community service activity is to form the Gemas Si Botak innovation program (Joint Movement for Booster Immunization in Children). The booster immunization program is included in the routine immunization program by giving 1 dose of DPT-HB-HiB and measles or MR to children aged 18-24 months. Giving booster doses of immunization to increase children's immunity because basic immunization alone is not enough. Optimal protection from giving this booster immunization is only obtained if the child has received complete basic immunization. Community service is carried out in January – March 2022. The target in this Gemas Si Botak program is mothers who have children aged less than 2 years, a total of 29 mothers. There is an increase in the knowledge of mothers who have children under 2 years of age from 27.6% with good knowledge to 89.7%. The output of the Gemas Si Botak program is the formation of cadres who are careful and always monitor the implementation of the 18-month booster immunization and people who are aware of the need to can provide the best protection to their children through the 18 month booster immunization.